2013
DOI: 10.1007/s00431-013-2163-8
|View full text |Cite
|
Sign up to set email alerts
|

Transient leukemia in a newborn without Down syndrome: case report and review of the literature

Abstract: Our case of transient leukemia without Down syndrome and the literature review highlight the important role of trisomy 21 and GATA1 mutation in the development of transient neonatal leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 34 publications
0
20
0
1
Order By: Relevance
“…GATA1 mutation testing was not routinely conducted in previously reported neonates with TAM and nonconstitutional trisomy 21 . Rozen et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…GATA1 mutation testing was not routinely conducted in previously reported neonates with TAM and nonconstitutional trisomy 21 . Rozen et al.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19] Rozen et al performed a literature review of 14 patients with TAM that was not associated with DS and reported that GATA1 mutations were analyzed in only eight patients, all of whom had GATA1 mutations as well as trisomy 21 in leukemic blasts, indicating that the biology of TAM without constitutional trisomy 21 was similar to that of TAM with constitutional trisomy 21/DS. 19 After the report of Rozen et al, there have also been several case reports of TAM without constitutional trisomy 21 but harboring both trisomy 21 and GATA1 mutations in leukemic blasts. [21][22][23][24] Here, we present the cytogenetic findings and GATA1 mutation status of a series of 17 patients with TAM and nonconstitutional trisomy 21 who had been tested for GATA1 mutations at a single institute.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While TAM is classically described as being unique to DS patients, rare cases of TAM have been reported in the absence of phenotypic DS, usually in patients with either mosaic or partial trisomy 21. Even fewer cases have been reported with trisomy 21 restricted to the blast cells ; when tested these cases have been positive for GATA1 mutation, further implicating GATA1 and chromosome 21 in the pathogenesis of TAM . The exact means by which the truncated GATA1 protein and additional genetic material from chromosome 21 cause these transient proliferations, and confer an increased risk of subsequent AML, remains unknown.…”
mentioning
confidence: 99%